Botulinum neurotoxin for head and neck disorders - Blitzer, Andrew; Benson, Brian E.; Kirke, Diana N. (Thieme, 2020)
"Senior author Dr. Andrew Blitzer is an internationally renowned pioneer on the use of botulinum neurotoxin for functional disorders, with unparalleled expertise on this topic. Joined by co-editors Brian Benson and Diana Kirke, with multidisciplinary contributors, Botulinum Neurotoxin for Head and Neck Disorders Second Edition fills a gap in the medical literature. The unique textbook focuses on the use of botulinum neurotoxins for functional disorders of the head and neck, though with some aesthetic indications. The second edition reflects the latest advances and understanding of existing and emerging applications for botulinum neurotoxins, including new treatment paradigms, revised pharmacology, and an updated review of the literature in all chapters. Twenty superbly illustrated chapters cover the management of hyperfunctional, pain, and hypersecretory syndromes of the head and neck. Hyperfunctional motor disorders are discussed in chapters focused on blepharospasm, facial dystonia, Meige syndrome, oromandibular dystonia, spasmodic dysphonia (laryngeal dystonia), and cervical dystonia. Specific treatment approaches for pain are addressed in chapters on migraine and chronic daily tension headaches, temporomandibular disorders, and trigeminal neuralgia. The treatment of autonomic nervous system disorders is covered in chapters dedicated to Frey syndrome, facial hyperhydrosis, and sialorrhea"--